حرفة صياغة الذهب المعاصرة في مدينة الديوانية: مقاربة أنثروبولوجية - ناصر، عدنان مطر (كلية الامارات للعلوم التربوية, 2021)
إن هدف البحث معرفة ما وصل إليه فن صياغة الذهب في المجتمع العراقي بشكل عام والمجتمع المحلي (مدينة الديوانية إنموذجًا) بشكل خاص من تطورات في طبيعة مواد وأساليب وتقنيات التكنولوجية الحديثة في تطوير الصياغة باطار أنثروبولوجي داخل السوق الكبير في المدينة القديمة التي تمثل قلب ومركز محافظة القادسية من وجهة نظر عينة من صاغة محلات الذهب والصناع العاملين معهم والبالغ عددهم (20) صائغ و (40) صانع ماهر وشبه ماهر اعتمادًا على المنهج الأنثروبولوجي بطريقة العينة العمدية كمجال للبحث واستعمال الأدوات المناسبة للمنهج الأنثروبولوجي كالمقابلة والملاحظة والمخبرون لجمع المعلومات وتوصل البحث إلى مجموعة من الاستنتاجات أهمها دخول الميكنة الحديثة والكهرباء والقوالب الجاهزة كأدوات يعتمد عليها الصائغ في عمله بعد أن كان عمله يدوي. وقادت إلى عدد من التوصيات منها ضرورة العمل لتطوير صناعة وصياغة الذهب في المدينة لإيجاد صناعات عراقية ومحلية ذات أهمية استراتيجية تنافس الصناعات الأجنبية. The aim of the research is to know what the art of goldsmithing has reached in the Iraqi local community (Al-Diwaniyah city as a model) of developments in the nature of materials, methods and techniques of modern technology in the development of goldsmithing with an anthropological framework within the big market in the old city, which represents the heart and center of Al-Qadisiyah Governorate from the point of view of a sample From the goldsmiths of the gold shops and the craftsmen working with them, who number (20) goldsmiths and (40) skilled and semi-skilled craftsmen, depending on the anthropological method in the method of the intentional sampling as a field of research, and using the appropriate tools for the anthropological method such as interview, observation and informants to collect information. The research reached a set of conclusions, the most important of which is the entry of modern mechanization, electricity and ready-made molds as tools that the goldsmith relies on in his work after his work was manual. And it led to a number of recommendations, including the need to work to develop the gold industry and forge to create local Iraqi industries of strategic importance to compete with foreign industries.
Keywords: علم الإنثروبولوجية -- حرفة صياغة الذهب -- مدينة الديوانية -- العراق